An Analysis of the Second Year English Department Students' Errors in Using Passive Voice in the Academic Writing Subject of Universitas Negeri Padang - Paradise Princess; Saunir Saun; Aryuliva Adnan (Universitas Negeri Padang, 2018)
This research was aimed at analyzing the errors made by the second year English department students in using passive voice in the Academic Writing Subject. Specifically, it was aimed at finding the types of errors and the causes of errors made by the students in their academic writings. This research was a descriptive qualitative research. The sample of this research was the K3 students consisting of 19 students. The sample was taken based on the cluster sampling technique. Then, the students’ academic writings were used as the source of the data. The data collection was taken by using the theory of Surface Structure Taxonomy proposed by Dulay et al. (1982). Related to the causes of errors, the theory proposed by James and Brown was used to study the causes of errors made by the students. The findings show that there were 367 errors made by the students. The highest type of errors made by the students was 216 omission errors (59%) and followed by 104 misformation errors (28%), 34 addition errors (9%), and 13 misordering errors (4%). It was found that the major causes of errors were interlingual and intralingual factors. Based on the findings, it can be concluded that the students did the four types of errors.